Gold mediated glycosylations: selective activation of propargyl 1,2-orthoesters in the presence of aglycones containing a propargyl moiety - Sureshkumar, Gopalsamy; Hotha, Srinivas (Chemical Communications, 2008)
Selective activation of propargyl 1,2-orthoesters in the presence of propargyl glycosides and propargyl ethers was studied; a catalytic amount of AuBr(3) activated the propargyloxy, group of the 1,2-orthoester thereby giving access to disaccharides with the propargyl group at the reducing end; furthermore, propargyl ethers were unaffected under the reaction conditions.